Perancangan Sistem Pengaduan Masyarakat Berbasis Mobile (Studi Kasus : Kabupaten Banjarnegara) - Karim, Al Bahrul; Fachrie, Muhammad (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
In this digital era, public complaint services are very important to increase public participation in governance management. However, there are still many obstacles faced by the public in filing complaints, such as difficulty in finding information on complaint services, complicated complaint processes, or lack of transparency in complaint handling. To overcome these problems, the author developed a public complaint service application in Banjarnegara District which allows residents to file complaints online. This solution is expected to be able to connect the authorities with the community more effectively and efficiently. Preliminary results show this application is expected to increase public participation in governance management and improve the effectiveness of complaint services. The features provided include online reporting, easy to access and operate, as well as facilities for managing complaint data and reports that are useful for relevant agencies in handling complaints.